2016
DOI: 10.1177/0284185116631180
|View full text |Cite
|
Sign up to set email alerts
|

Improvements to image quality using hybrid and model-based iterative reconstructions: a phantom study

Abstract: There is great potential to reduce noise and thereby improve image quality by using hybrid or, in particular, model-based iterative reconstruction methods, or to lower radiation dose and maintain image quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
(36 reference statements)
8
6
0
Order By: Relevance
“…Noise and uniformity within all image acquisition protocols also conformed to the requirements of the American College of Radiology [15]. In agreement with a previous study utilizing a Catphan image quality phantom [22], image quality assessment demonstrated that CT numbers were not affected by IR settings.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Noise and uniformity within all image acquisition protocols also conformed to the requirements of the American College of Radiology [15]. In agreement with a previous study utilizing a Catphan image quality phantom [22], image quality assessment demonstrated that CT numbers were not affected by IR settings.…”
Section: Discussionsupporting
confidence: 87%
“…However, other institutions prefer to practice on the side of caution and report only 15% dose reduction for CT head [25]. With the combination of novel dose-reducing strategies such as model-based reconstruction methods [22,26] and noise efficient detectors [27], there is likely to be further significant dose reduction in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Phantoms have been widely applied in medical imaging, especially in CT systems, commonly for both quantitative and qualitative assessments of image quality. Many prior studies [12][13][14] have highlighted the advantages of using phantoms, especially when the investigations involve multiple radiation exposures with different acquisitions settings. One of the most common phantoms used for the investigations of CT protocols is the anthropomorphic chest phantom (Kyoto Kagaku, Japan).…”
Section: Introductionmentioning
confidence: 99%
“…Imaging phantoms are widely used as a tool for assessing the performance of IR algorithms for dose reduction in CCTA scans. Many phantoms, such as the Catphan â (The Phantom Laboratory, Salem, NY) phantom, used in the previous studies [9][10][11] to provide a good first-order approximation of image quality. However, it is possible that such phantoms are not fully adequate to assess the impact of IR algorithms due to their current shape, the complexity of IR algorithms and the different types of patient body habitus, which can influence the radiation dose during CCTA scans.…”
Section: Introductionmentioning
confidence: 99%